Demographic, psychological and smoking characteristics of users of an on-line smoking cessation programme in the Spanish language - Guillermo Mañanes; Miguel A. Vallejo; Laura Vallejo-Slocker (Elsevier, 2016)
Objective: To determine the characteristics of users of a smoking cessation programme run by the Open University of Spain (Universidad Nacional de Educación a Distancia [UNED]). Methods: We examined the demographic, psychological and smoking characteristics of 23,763 smokers who participated in the on-line smoking cessation program of the UNED. The programme was open to any smoker, free of charge, and was fully automated and with direct access. Results: A total of 93.5% of the users were Spaniards, with an equal percentage of participation among men and women. The mean age was 39 years. Somewhat less than half were married and had a university education. The participants smoked a mean of 19.3 cigarettes per day, showing a mid-range level of nicotine dependence according to the Heaviness of Smoking Index. The results of the Anxiety and Depression subscales of the Symptom Checklist-90-Revised (SCL-90-R) and Perceived Stress Scale were not clinically significant. In a secondary analysis of the data, we found gender differences in all the variables measured. Conclusions: The results of this study confirm the digital divide, with lower participation among people with a lower educational level. No association was observed between stress, anxiety or depression and cigarette consumption.